KRAS Mutational Regression Is Associated With Oligo-Metastatic Status and Good Prognosis in Metastatic Colorectal Cancer - Ottaiano, Alessandro; Nasti, Guglielmo; Santorsola, Mariachiara; Altieri, Vincenzo; Di Fruscio, Giuseppina; Circelli, Luisa; Luce, Amalia; Cossu, Alessia Maria; Scognamiglio, Giosuè; Perri, Francesco; Correra, Marco; Belli, Andrea; et al. (Frontiers in Oncology, 2021)
Background. We previously reported that loss of KRAS mutations (“regressive” mutational trajectories) from primary tumors to metastases associated with the oligo-metastatic status in colorectal cancer (CRC). The present study was undertaken in order to analyze the mutational trajectories of KRAS in a well-characterized cohort of CRC patients who developed poly- or oligo-metastatic disease. Material and Methods. Patients were treated and followed-up according to European Society of Medical Oncology guidelines. Primary CRC FFPE tissue and metastatic circulating-free DNA were extracted using the QIAamp DNA specific kits (Qiagen, Hilden, Germany). Samples were sequenced with the Oncomine Solid Tumour DNA kit (Thermo Fisher Scientific, Waltham, MA, USA). Plasma collection for liquid biopsy was done from 1 to 14 days before starting first-line chemotherapy. Analysis of the prognostic power of KRAS evolutionary trajectories was done with uni- and multivariate analyses. Results. One-hundred-fourteen patients were enrolled. Sixty-three patients presented with mutated KRAS (mutKRAS) and 51 with wild-type KRAS (wtKRAS). KRAS mutational concordance was high (70.1%). Two divergent subsets were identified: mutKRAS in primary tumors and wtKRAS in metastatic ones (regressive: mutKRAS→wtKRAS in 8.8% of patients), and viceversa (progressive: wtKRAS→mutKRAS in 21.1% of patients). An association between KRAS regressive trajectory and the oligo-metastatic status (P<0.0001) was found. At multivariate analysis, regressive and progressive mutational trajectories emerged as independent prognostic factors for survival, with Hazard Ratios of 0.22 (CI 95%: 0.08-0.61; median survival: not reached) and 2.70 (CI 95%: 1.11-6.56, median survival: 12.1 months), respectively. Conclusions. Our data provide evidence that the evolutionary trajectories of KRAS can have a strong clinical prognostic role and that they can be involved in discriminating between poly-metastatic aggressive vs oligo-metastatic indolent CRC.